Metabolomics study of APETx2 post-conditioning on myocardial ischemia-reperfusion injury - Li, Jing; Wei, Yiyong; Wang, Yi; Zhang, Yue; Xu, Ying; Ma, Huanhuan; Ma, Lulin; Zeng, Qingfan (Frontiers in Pharmacology, 2024)
Background: Acid-sensing ion channels are activated during myocardial ischemia and are implicated in the mechanism of myocardial ischemia-reperfusion injury (MIRI). Acid-sensing ion channel 3 (ASIC3), the most pH-sensitive member of the ASIC family, is highly expressed in myocardial tissues. However, the role of ASIC3 in MIRI and its precise effects on the myocardial metabolome remain unclear. These unknowns might be related to the cardioprotective effects observed with APETx2 post-conditioning.Method: Rat hearts subjected to Langendorff perfusion were randomly assigned to the normal (Nor) group, ischemia/reperfusion (I/R) group, ASIC3 blockade (AP) group. Rat hearts in group AP were treated with the ASIC3-specific inhibitor APETx2 (630 nM). Molecular and morphological changes were observed to elucidate the role of ASIC3 in MIRI. Bioinformatics analyses identified differential metabolites and pathways associated with APETx2 post-conditioning. Results: APETx2 post-conditioning stabilized hemodynamics in the isolated rat heart model of MIRI. It also reduced myocardial infarct size, mitigated mitochondrial damage at the ultrastructural level, and improved markers of myocardial injury and oxidative stress. Further more, we observed that phosphatidylcholine, phosphatidylethanolamine, citric acid, cyanidin 5-O-beta-D-glucoside, and L-aspartic acid decreased after MIRI. The levels of these metabolites were partially restored by APETx2 post-conditioning. These metabolites are primarily involved in autophagy and endogenous cannabinoid signaling pathways. Conclusion: ASIC3 is potentially a key player in MIRI. APETx2 post-conditioning may improve MIRI through specific metabolic changes. This study provides valuable data for future research on the metabolic mechanisms underlying the effects of APETx2 post-conditioning in MIRI.